MENELAAH KEMBALI GAGASAN PEMIKIRAN DAN PERJUANGAN AHMAD SYAFII MAARIF JALAN TENGAH KEBERAGAMAN - Wandi Wandi; M Arif Musthofa; Khusnul Yatima (Keraton: Journal of History Education and Culture, 2019)
This research was specifically written as a result of reflection on diversity in Indonesia at this time, where friction in the name of ethnicity, race, religion and even the issue of state always appear in the public sphere, departing from the problem above, the author wants to "re-examine ideas, thoughts and Ahmad SyafiiMaarif's struggle for a middle path of diversity" a search for solutions to the problemsas the writer has mentionedabove. This type of research was a literature study by collecting primary books about the works and thoughts of Ahmad SyafiiMaarif both written by himself and written by others. The result was an important key to realizing a glorious Islamic civilization in Indonesia. Integration between Islam, Indonesia and humanity is urgently needed where these three issues must be resolved in order to stem the friction, for the achievement of a friendly Islam, providing security, security and protection of the inhabitants of the archipelago in a humanitarian frame.